Halal-Based Entrepreneurship Development for Menteng MSME Community Industry - Desmintari; Lina Aryani; Dahlia Pinem (PT FORMOSA CENDEKIA GLOBAL, 2023)
Menteng District is located in the administrative area of ​​Central Jakarta City, DKI Jakarta Province. Partners who become objects are MSME actors in the Menteng “Naik Kelas” MSME Community. Currently, the development of products produced by MSME actors has not been maximized. This is because partners have not applied the principles of the halal industry to their products. The goal to be achieved from this community service activity is to improve product quality by guiding partners to develop products based on the halal industry. In general, the method of service carried out to partners is in the form of socialization/virtual counseling related to the halal industry and their product development based on the principles of the halal industry. It is hoped that this training can improve competitiveness and product quality so as to increase the sales volume of products made by the Menteng